(untitled) (GIST – Education and Learning Research Journal, 2021)
Language learning that is grounded on learners’ sociocultural realities promises to be a meaningful experience they are likely to treasure when it comes to grappling with practical day-to-day matters. This article reports on a research study aimed at fostering socioculturally constructed language learning in a group of pre-service English teachers. This is a qualitative case study, grounded in a social constructivist paradigm, which draws on a pedagogy of multiliteracies through the Knowledge Process and the Concept of Design (Cope & Kalantzis, 2009) to embrace diverse modes of communication and to expand learners’ possibilities of engagement with text and the social and cultural world around them. The findings indicate that while learners are provided with opportunities to explore, reflect and co-construct socioculturally driven knowledge, they are involved in a meaning-making experience that allows them to make sense of the language they are learning.